2020
DOI: 10.3390/nu12092662
|View full text |Cite
|
Sign up to set email alerts
|

A Call to Action: Now Is the Time to Screen Elderly and Treat Osteosarcopenia, a Position Paper of the Italian College of Academic Nutritionists MED/49 (ICAN-49)

Abstract: Aging is a risk factor for the development of multiple chronic diseases, including cardiovascular disease, cancer and dementia. Life expectancy has increased in certain countries but this phenomenon is associated with a reduction of years of healthy life. Aging is associated with a number of physical and functional changes, especially sarcopenia. Sarcopenia is a clinical condition associated with a decrease in skeletal muscle and muscle strength, however, sarcopenia is a reversible condition. On the basis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 191 publications
(234 reference statements)
0
8
0
2
Order By: Relevance
“…In fact, previous studies showed that physical activity had a positive effect on muscle mass and function in elderly individuals [78,79]. Furthermore, protein intake was associated with a low risk of sarcopenia [60,80,81]. As previously reported [16], overweight/obese older individuals would likely benefit more from losing excess adiposity than building muscle mass, while normal-weight people would likely benefit more from maintenance or building muscle.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In fact, previous studies showed that physical activity had a positive effect on muscle mass and function in elderly individuals [78,79]. Furthermore, protein intake was associated with a low risk of sarcopenia [60,80,81]. As previously reported [16], overweight/obese older individuals would likely benefit more from losing excess adiposity than building muscle mass, while normal-weight people would likely benefit more from maintenance or building muscle.…”
Section: Discussionmentioning
confidence: 71%
“…All these previous findings agree with our results demonstrating an important role of ASMM in predicting IGF/T2D in elderly women. As skeletal muscle is responsible for the majority of postprandial glucose disposal in the body, dysfunction of this part of the body might result in substantial whole-body metabolic disorders [60]. Physical inactivity, which is a common feature of aging, is associated with a decline in mitochondrial oxidative function in muscle [61].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the great advantages offered by imaging tools in research and clinics, the focus of clinicians is now moving to powerful imaging techniques such as computed tomography (CT), magnetic resonance (MR) imaging, dual-energy X-ray absorptiometry (DXA), or other techniques such as bioimpedance analysis (BIA) and ultrasound (US) to more accurately measure FM ( 38 ). Although some of the above methods can be expensive, in some cases invasive, and not readily accessible, they are more accurate at measuring body fat, and thus better at predicting the risk of obesity-related health issues.…”
Section: Novel Nutritional Biomarkers Of Non-communicable Diseasesmentioning
confidence: 99%
“…Skeletal muscle is responsible for the majority of the body's postprandial glucose disposal, and insulin mediates GLUT-4 glucose uptake in skeletal muscle. Therefore, the potential mechanisms linking sarcopenia to NAFLD may involve skeletal muscle insulin resistance (32) . The findings of our research also suggest another possible mechanism.…”
Section: Discussionmentioning
confidence: 99%